Concussion symptoms among icelandic female athletes : concussion symptoms and connection to age at first concussion - Sunna Baldvinsdóttir 1997- (2020)
The purpose of this study was to examine if age is an important factor when looking at long term affects of a concussion, recovery time after first concussion and concussion count. The purpose of these writings is to encorage and enlighten individuals about the importance of being more careful when young children sustain a concussion. This study tested three hypotheses. The first one suggested that it takes children more time to recover from their first concussion. The second hypothesis suggested if age, when the first concussion occurred, correlates with concussion count later in life. The third hypothesis suggested that younger age at first concussion corresponds with current post-concussion symptoms. The data was acquired from a study conducted in 2018, Concussion Among Female Athletes In Iceland – A Multi-Component study. Participants were 166 and the age span was from 17 to 45 years old. The questionnaire that was used was The Sport Concussion Assessment Tool 5th Edition (SCAT5). SCAT is a tool for clinicians and the public when assessing sports-related concussion (SRC). For this study the list was translated from English to Icelandic. The results showed that children are not significantly longer to recover from a concussion than adults. It also indicated that age significantly correlates with total concussion count later in life and younger age at first concussion corresponds with current post-concussion symptoms. Tilgangur rannsóknarinnar var að athuga hvort að aldur eftir fyrsta heilahristing væri mikilvægur þáttur þegar skoðað er langtíma einkenni, hversu flljót börn eru að jafna sig á einkennum eftir fyrsta heilahristing, einkenni eftir fyrsta heilahristing, heilahristingsfjölda. Með þessari rannsókn er vonast til að fólk verði meira upplýst um mikilvægi þess að fara varlega þegar barn verður fyrir höfuðhöggi. Í þessari rannsókn voru þrjár tilgátur settar fram. Fyrsta tilgátan gekk út á það að börn séu lengur að jafna sig eftir sinn fyrsta heilahristing. Önnur tilgáta skoðaði hvort að aldur við ...